Peran Komunikasi Efektif di SMPN 12 Bandung dengan Masyarakat dalam Mendukung Pembelajaran Siswa - Mazaya Faudya Nur Aufa; Wini Anisa Apriliani; Khansa Aulia Syahidah; Nelly Kristin Sibarani (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
Effective communication between schools and the community is an essential element in supporting student learning success. This study aims to describe the role of effective communication between SMPN 12 Bandung and the community in facilitating student learning. A descriptive qualitative approach was employed, with data collected through interviews and observations. Data analysis followed three main stages: data reduction, data presentation, and conclusion drawing/verification. The study's subject was the vice principal in charge of public relations. The findings indicate that communication between SMPN 12 Bandung and the community is well-established, enabling the school to implement various programs and activities to support student learning. These findings underscore the importance of effective communication as a means to strengthen collaboration between schools and the community. Good communication not only ensures the successful implementation of educational programs but also fosters a conducive learning environment and encourages active student participation in learning. Thus, effective communication serves as a key pillar in building collaboration among schools, the community, and students to achieve educational goals.